Analysis of Gross Regional Domestic Product, Population, and Tourism: How Do They Impact the Regional Original Revenue of Yogyakarta Province? (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to analyze the effect of Gross Regional Domestic Product (Produk Regional Domestik Bruto/PDRB), population, and tourism sector on the regional original revenue of the Special Region of Yogyakarta. This quantitative research compiled research data that were measured and tested using numerical data. This study used secondary data from the Financial and Asset Management Agency of the Special Region of Yogyakarta Province from 2014 – 2023. The data analysis of this study used SPSS 26 software. The results of this research, with significance value (sig.